INFLUENCES OF LAMP IRRADIATION EXPOSURE ON GROWTH AND SURVIVAL OF JUVENILE SNEAKHEAD FISH Channa striata (Bloch, 1793) - Triyanto, Triyanto; Tarsim, Tarsim; Utomo, Deny Sapto Chondro (e-Jurnal Rekayasa dan Teknologi Budidaya Perairan, 2020)
The research has been conducted by February to March 2018 in the Laboratory of Aquaculture, Faculty of Agriculture, Lampung University. The research aim of this to acknowledge the influences of lamp irradiation exposure on growth and survival of juvenile sneakhead fish (Channa striata). This research used a completely randomized design with five treatments, A (12B;12D), B (9B;15D), C (6B;18D), D (3B;21D), and E (0B;24D) with three replications. The research showed that the effect of the length of light irradiation exposure has a significant effect on growth and survival of juvenile snakehead fish. The best treatment found in treatment D, that the resulted highest value of weight growth (5,46 g), daily weight growth (0,121 g/day), length growth (5,37 cm), daily length growth (0,119 cm/day), and survival rate of 97%.